A comparative study of blood alcohol concentrations in Australian night-time entertainment districts - Miller, P.; Pennay, A.; Droste, N.; Butler, E.; Jenkinson, R.; Hyder, S.; Quinn, B.; Chikritzhs, Tanya; Tomsen, S.; Wadds, P.; Jones, S.; Palmer, D.; et al. (Wiley-Blackwell Publishing Ltd., 2014)
Introduction and Aims: There is little research describing how intoxication levels change throughout the night in entertainment districts. This research aims to describe levels of alcohol intoxication across multiple Australian metropolitan and regional nightlife districts. Design and Methods: This study was conducted in the night-time entertainment districts of three metropolitan cities (Sydney, Melbourne and Perth) and two regional cities (Wollongong and Geelong) in Australia. Data collection occurred approximately fortnightly in each city on a Friday or Saturday night between 8 PM and 5 AM. Brief structured interviews (3–10 min) and breathalyser tests were undertaken in busy thoroughfares over six months. Results: Of the 7037 individuals approached to participate in the study, 6998 [61.8% male, mean age 24.89 years (standard deviation6.37; range 18–73)] agreed to be interviewed. There was a linear increase in blood alcohol concentration (BAC) levels throughout the night. Post hoc testing revealed significantly more highly intoxicated participants (i.e. BAC above 0.10 mg of alcohol per 100 mL of blood) after midnight (P < 0.05). The overall mean BAC was 0.06 mg/100 mL. Men were more intoxicated than women earlier in the night, but gender differences disappeared by 3 AM. There was no age difference in intoxication earlier in the night, but after midnight, patrons over the age of 21 showed increasing BAC levels. Discussion and Conclusions: There is a consistent trend across the cities of high to very high levels of intoxication later in the night, with trends after midnight being significantly different to those before.